2015
DOI: 10.4172/2155-9899.1000381
|View full text |Cite
|
Sign up to set email alerts
|

The TH17/Treg Imbalance in Rheumatoid Arthritis and Relation to Disease Activity

Abstract: Objectives: T regulatory cells (Treg) and proinflammatory T H 17 cells are newly identified T lymphocyte subsets, which have significant effects on autoimmunity and inflammation. Tregs play key role in the maintenance of selftolerance. T H 17/Treg disturbed balance has been reported to contribute to several autoimmune diseases. Our aim was to assess the Treg/T H 17 pattern and T H 17 related cytokines, in peripheral blood of Egyptian rheumatoid arthritis patients, and their relation to disease activity score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…At first, flow cytometric results of RA patients revealed a significantly lower percentage of circulating CD4 + Foxp3 + CD25 high Tregs as compared to healthy controls. Similarly, our findings are consistent with most studies, although the authors have presented various conclusions [19-21]. A major differences between studies could be a result of the definition of Tregs in flow cytometric gating patterns [22-24].…”
Section: Discussionsupporting
confidence: 92%
“…At first, flow cytometric results of RA patients revealed a significantly lower percentage of circulating CD4 + Foxp3 + CD25 high Tregs as compared to healthy controls. Similarly, our findings are consistent with most studies, although the authors have presented various conclusions [19-21]. A major differences between studies could be a result of the definition of Tregs in flow cytometric gating patterns [22-24].…”
Section: Discussionsupporting
confidence: 92%
“… 26 On the other hand, Treg cells suppress pro‐inflammatory responses by inhibiting the activation of T cell subsets including Th1 and Th17. 25 As expected, we observed that the populations of Th17 cells were elevated whereas the populations of Treg cells were reduced in the CIA mouse model. These characteristics are in agreement with the previous findings, where a shift in the Th17/Treg cell to the Th17 cell side leads to RA with more severe symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…Both Th17 and Treg cells are known to have important roles in the RA, as supported by Th17/Treg imbalance observed in preclinical and clinical studies of RA 14,25 . Th17 cells are known to mediate bone destruction and promote joint inflammation in part by secreting IL‐17 26 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…who reported an elevated serum Foxp3 more in patients than control group (51% vs 18%, respectively). 17 Higher and lower mean Foxp3 levels were reported by Alzifzaf et al 19 and Gaafar et al 22 (16.9 and 1.01 ng/ml in patients with rheumatoid arthritis vs 26.4 and 1.72 ng/ml in control subjects, respectively).…”
Section: Discussionmentioning
confidence: 76%